2016
DOI: 10.1155/2016/6232036
|View full text |Cite
|
Sign up to set email alerts
|

PPARαAgonist Fenofibrate Reduced the Secreting Load ofβ-Cells in Hypertriglyceridemia Patients with Normal Glucose Tolerance

Abstract: Hypertriglyceridemia is an important risk factor associated with insulin resistance and β-cell dysfunction. This study investigated the effects of hypertriglyceridemia and fenofibrate treatment on insulin sensitivity and β-cell function in subjects with normal glucose tolerance. A total of 1974 subjects with normal glucose tolerance were divided into the normal TG group (NTG group, n = 1302) and hypertriglyceridemia group (HTG group, n = 672). Next, 92 patients selected randomly from 672 patients with hypertri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Importantly, fenofibrate treatment administered to the IGT patients with hypertriglyceridemia for 12 weeks resulted in the significant decrease in FINS, HOMA2-%B, and HOMA2-IR and the significant increase in HOMA2-%S and McA; the change in TG was inversely related to the change in McA. Our findings are similar to the previous studies in hypertriglyceridemic patients with prediabetes [12] or with NGT [13]. However, our findings are in contrast to some recent studies in nondiabetic individuals with insulin resistance [14] or in subjects with T2DM [15, 16].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Importantly, fenofibrate treatment administered to the IGT patients with hypertriglyceridemia for 12 weeks resulted in the significant decrease in FINS, HOMA2-%B, and HOMA2-IR and the significant increase in HOMA2-%S and McA; the change in TG was inversely related to the change in McA. Our findings are similar to the previous studies in hypertriglyceridemic patients with prediabetes [12] or with NGT [13]. However, our findings are in contrast to some recent studies in nondiabetic individuals with insulin resistance [14] or in subjects with T2DM [15, 16].…”
Section: Discussionsupporting
confidence: 89%
“…Most studies have indicated the insulin-sensitizing actions of fenofibrate, although the actions have been questioned by other studies. Some studies have demonstrated that fenofibrate exerted protective effects on hypertriglyceridemic patients with prediabetes [12], and ameliorated insulin resistance in hypertriglyceridemic patients with normal glucose tolerance (NGT) [13]. On the contrary, other studies have found that fenofibrate has no effects on the insulin sensitivity in insulin-resistant nondiabetic subjects [14] or in subjects with T2DM [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated in multiple animal studies that fenofibrate reduces albuminuria in patients with diabetes [25,61,87] . In addition to reducing albuminuria, fenofibrate has been reported to ameliorate hyperglycemia [88,89] . Acute fibrate-induced creatinine elevation in T2D with relatively preserved renal function may confer longer-term renoprotective effects.…”
Section: Metabolic Nuclear Receptors: Great Promise?mentioning
confidence: 99%
“…Several studies have shown that peroxisome proliferator-activated receptor α (PPARα) agonist could inhibit renal inflammation and fibrosis and prevent renal oxidative stress [11][12]. Our previous studies have shown that fenofibrate therapy can significantly reduce insulin resistance and the secretory load of β cells [2]. Fenofibrate could improve plasma levels of tetrahydrobiopterin (BH4) by increasing the guanosine 5-triphosphate cyclohydrolase-I expression and protect endothelial function [3][4].…”
Section: Discussionmentioning
confidence: 99%